Complete genome sequence of Staphylococcus haemolyticus type strain SGAir0252 - Premkrishnan, Balakrishnan N. V. (2019)
Staphylococcus haemolyticus is a coagulase-negative staphylococcal species that is part of the skin microbiome and an opportunistic human pathogen. The strain SGAir0252 was isolated from tropical air samples collected in Singapore, and its complete genome comprises one chromosome of 2.63 Mb and one plasmid of 41.6 kb.